Groundwater contamination and analysis at hazardous waste sites - Lesage, Suzanne; Jackson, R. E. (Richard E.) (Environmental science and pollution control series, 1992)
Describes investigations of the fate of toxic chemicals emanating from hazardous waste sites and contaminating groundwater, discussing the hydrogeochemistry at US, Canadian, Australian, and German sites to reflect the different approaches used around the world. It is suitable for pollution control and environmental engineers and hydrogeologists.